Comparison of the Standard vs. Thoracoscopic Extrapleural Modification of the Nuss Procedure-Two Centers' Experiences - Miloš Pajić; Damjan Vidovič; Radoica Jokić; Jelena Antić; Nenad Čubrić; Ivana Fratrić; Svetlana Bukarica; Aleksandar Komarčević; Marina Milenković (MDPI AG, 2022)
Pectus excavatum is the most common congenital anterior chest wall deformity, with an incidence of 1:400 to 1:1000. Surgical strategy has evolved with the revolutionary idea of Donald Nuss, who was a pioneer in the operative correction of this deformity using minimally invasive surgery. The aim of this paper is to compare the preliminary results of pectus excavatum repair in two University Centers with a moderate number of patients using the standard Nuss procedure and its modification, the extrapleural thoracoscopic approach. The statistical analysis showed no significant difference for the patient's age (14.52 ± 3.70 vs. 14.57 ± 1.86; p = 0.95) and the CT Haller index (4.17 ± 1.58 vs. 3.78 ± 0.95; p = 0.32). A statistically significant difference was noted for the duration of a pectus bar implant (2.16 ± 0.24 vs. 2.48 ± 0.68; p = 0.03) between the Maribor and Novi Sad Center. We report 14 complications (28%), including dislocation of the pectus bar (10%), pleural effusion (8%), wound inflammation (6%), pericarditis (2%) and an allergic reaction to the pectus bar (2%). Standard and thoracoscopic extrapleural Nuss procedures are both safe and effective procedures used to correct a pectus excavatum deformity. The choice of surgical procedure should be made according to a surgeon's reliability in performing a particular procedure. Our study found no advantages of one procedure over the other.